2019
DOI: 10.1101/845156
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise spatial spatial memory in local random networks

Abstract: Self-sustained, elevated neuronal activity persisting on time scales of ten seconds or longer is thought to be vital for aspects of working memory, including brain representations of real space. Continuous-attractor neural networks, one of the most well-known modeling frameworks for persistent activity, have been able to model crucial aspects of such spatial memory. These models tend to require highly structured or regular synaptic architectures. In contrast, we elaborate a geometrically-embedded model with a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…One of our results is that selectivity can emerge for task parameters from an unstructured, random network. Several theoretical studies have previously examined the emergence of selectivity in random networks [23,[25][26][27][28][29][30]. As early as the 1970s, it was suggested that orientation selectivity in primary visual cortex could emerge from random projections from geniculate inputs [25,26].…”
Section: Relationship To Other Network Modelsmentioning
confidence: 99%
“…One of our results is that selectivity can emerge for task parameters from an unstructured, random network. Several theoretical studies have previously examined the emergence of selectivity in random networks [23,[25][26][27][28][29][30]. As early as the 1970s, it was suggested that orientation selectivity in primary visual cortex could emerge from random projections from geniculate inputs [25,26].…”
Section: Relationship To Other Network Modelsmentioning
confidence: 99%